Penerapan Model Pembelajaran Project Based Learning dalam Materi Menemukan Unsur Karya Fiksi di Kelas VIII SMP Negeri 12 Kota Jambi - Septian, Dwi Adjie; Kamaruddin, Kamaruddin; Rasdawita, Rasdawita (Jurnal Ilmiah Dikdaya, 2024)
This research aims to describe how the Project Based Learning Model is implemented in the material Finding Elements of Fiction Works for class VIII SMP Negeri 12 Jambi City. The formulation of this research problem is how teachers apply the Project Based Learning model in the material Finding Elements of Fiction Works. This research uses qualitative methods and descriptive research type. The data source in this research is a teacher who teaches in a class in the Indonesian language subject. The data in this research is divided into two, the results of field research and the results of documentation. Data collection techniques in this research include observation, interviews, tests, documentation. In testing the validity of the data using triangulation techniques. This research was conducted at SMP Negeri 12 Jambi City. This research was conducted in 3 meetings. The results of this research are (1) Essential Questions and Project Determination Activities, the Indonesian language subject teacher asks essential questions to students and the determination of the project to be carried out is to find elements in a work of fiction made in a poster. (2) Activities at the project planning design stage, at the planning stage are carried out collaboratively by both the teacher and all students. (3) Activities at the schedule preparation stage, activities at this stage create a timeline for project work and create a deadline for project completion. (4) Activities at the stage of monitoring students and project progress, the teacher will act as a mentor for student activities in working on the project. (5) Activities at the results testing stage are carried out to assist teachers in measuring students' intelligence and taking grades for project assignments. (6) Activities at the learning experience evaluation stage, so that each group can see the results of the project assignments carried out so that they can make improvements according to the teacher's suggestions. Project based learning can be used as a learning model now. Instill didactic values in students so they are not arrogant. The research results can be used as a reference source for other researchers who want to research the same research with different studies and can be used as a guide.